2001
DOI: 10.1067/mva.2001.117885
|View full text |Cite
|
Sign up to set email alerts
|

Durability of eversion carotid endarterectomy: Comparison with primary closure and carotid patch angioplasty

Abstract: This prospective, nonrandomized clinical study indicates that eversion CEA is an effective surgical option comparable to conventional CEA with either primary arteriotomy closure or carotid patch angioplasty. No differences were found between eversion CEA and these more widely accepted CEA closure techniques with respect to operative morbidity and mortality. These data indicate, however, that eversion CEA has a lower restenosis rate than conventional CEA closure techniques and thus superior long-term durability. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
43
0
4

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(50 citation statements)
references
References 28 publications
3
43
0
4
Order By: Relevance
“…However, longer operative time, and risk of rupture or aneurysm have been reported as disadvantages of patch plasty in some studies. [27,28] Myers et al compared patch plasty and primary closure in terms of restenosis. No significant difference was found, but study did not include females or patients whose internal carotid artery diameter ≤5 mm.…”
Section: Resultsmentioning
confidence: 99%
“…However, longer operative time, and risk of rupture or aneurysm have been reported as disadvantages of patch plasty in some studies. [27,28] Myers et al compared patch plasty and primary closure in terms of restenosis. No significant difference was found, but study did not include females or patients whose internal carotid artery diameter ≤5 mm.…”
Section: Resultsmentioning
confidence: 99%
“…Numerous studies have compared C-CEA with patching with E-CEA. [15][16][17][18][19][20][21][22][23][24]29 Perhaps the most important of these is EVEREST (Eversion carotid Endarterectomy versus Standard Trial study), a randomized prospective multicenter study first published in 1998. 18 With the exception of the EVEREST and the findings of a few other reports, 30,31 the majority of studies found E-CEA to be as effective or superior to C-CEA with regard to perioperative stroke and death.…”
Section: Discussionmentioning
confidence: 99%
“…18 With the exception of the EVEREST and the findings of a few other reports, 30,31 the majority of studies found E-CEA to be as effective or superior to C-CEA with regard to perioperative stroke and death. 13,16,19,22,24,29,[32][33][34] In the EVEREST trial, 1353 patients were randomly assigned to E-CEA or C-CEA with shunting and patch closure of the arteriotomy left to the discretion of the operating surgeon. The conventional group consisted of 419 patients with primary arteriotomy closure and 256 patients with patch angioplasty.…”
Section: Discussionmentioning
confidence: 99%
“…68 Many other authors report the same findings, and the testimonies are reasonably consistent in stating that the commonly observed shorter ischemic times with eversion CE are due to the technically easier and structurally shorter anastomosis. 9,41,45,56,75,81 The major reason for this is that the arteriotomy and repair are centered such that the operative field is less crowded, and concern about iatrogenic stenosis is essentially eliminated. This makes the suturing easier and more comfortable for the surgeon.…”
Section: Clamp Times and Cerebral Ischemiamentioning
confidence: 99%